Soft X-Ray Magnetic Scattering Studies of 3d Magnetic Morphology Along Buried Interfaces in Nife/Copd/Nife Nanostructures - Escrig-Murua, J; Oyarzun-Medina, S; Casagrande-Denardin, J (Nature Publishing Group, 2019)
With the continuing interest in new magnetic materials for sensor devices and data storage applications, the community needs reliable and sensitive tools for the characterization of such materials. Soft X-rays tuned to elemental absorption edges are a depth and element sensitive probe of magnetic structure at the nanoscale, and scattering measurements have the potential to provide 3D magnetic structural information of the material. In this work we develop a methodology in transmission geometry that allows one to probe the spatial distribution of the magnetization along the different layers of magnetic heterostructures. We study the in-plane/out-of-plane transition of magnetic domains in multilayer thin film systems consisting of two layers of NiFe top and bottom, and a 50 repeat Co/Pd multilayer in the centre. The experimental data are analysed by simulating scattering data starting from micromagnetic simulations, and we find that the out of plane domains of the Co/Pd multilayer intrude into the NiFe layers to a greater extent than would be expected from micromagnetic simulations performed using the standard magnetically isotropic input parameters for the NiFe layers. © 2019, The Author(s).